Problems with Object Permanence: Rethinking Traditional Beliefs Associated with Poor Theory of Mind in Autism - Lawson, Wenn B.; Dombroski, Brynn A. (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
Poor Theory of Mind (ToM) (or difficulties imputing mental states to self and others) [1], (See also [2-5]) is often blamed for certain responses and behaviour in autism. However, the Theory of Mind Task Battery requires an understanding of language, the use of cognitive skills, as well as the child’s motivation and attention to complete. All of these factors are either weak or under-developed in individuals with autism suggesting that this is not the best means to measure one’s understanding that other people have their own thoughts, plans, beliefs, or point of view. Behaviours like strong defiance, insistence on sameness, fear associated with sudden change and severe anxiety may be related to difficulties seeing beyond the ‘now’ [6]. This paper suggests that some of the stress and anxiety in the autism population may actually be due to delayed object permanence (OP) (knowing something may still exist even if it is out of sight), which can appear as poor ToM. This delay in establishing OP is governed by single focused attention. For more information on this concept see: Lawson, W. (2011) The passionate mind, JKP:London. Although ToM and OP are defined differently, this paper aims to show the relationship between them and how one concept can influence the other using examples in everyday life to illustrate how poor OP is associated with single focused attention, which detracts from the bigger picture.